Hubungan Kelekatan Guru dengan Siswa terhadap Motivasi Belajar Siswa Kelas 3 SD di SDN Kaligandu Serang - Ehan Fauzan Rahmatillah; Evi Afiati; Siti Muhibah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the relationship between teacher-student attachment and learning motivation of 3rd grade students at SDN Kaligandu Serang. Teacher-student attachment plays a crucial role in creating a supportive learning environment that nurtures students’ psychological development and academic enthusiasm. Employing a quantitative correlational approach, the study involved 40 elementary students as samples. Data were collected using a Guttman-scale questionnaire, validated and tested for reliability. The analysis was carried out using Pearson Product Moment correlation with SPSS assistance. The findings indicate a strong and significant positive relationship (r = 0.840) between teacher-student attachment and students' learning motivation. These results highlight the importance of fostering strong emotional bonds between teachers and students to enhance student motivation in the classroom context.